Aconitum wumengense (Ranunculaceae), a new species from Yunnan, China - Wang, Jia-Yan; He, Jun; Xu, Zhou-Feng; Meng, Jing; Liu, En-De; Wang, Hong (Phytotaxa, 2018)
Aconitum wumengense, a new species from Luquan county, central Yunnan, China, is described and illustrated. It is most closely similar to A. geniculatum in habit, but differs by the densely appressed pubescent (vs. glabrous) inflorescence rachis, pedicels and ovaries, and very short, not circinate (vs. obviously circinate) spur of petals.